Carotid Artery Disease in Anterior Circulation Strokes; A Retrospective Analysis using Doppler Ultrasound - Sarwat Iqbal, Shahzad Majeed Bhatti, Mujeeb Ur Rehman Abid Butt, Fatima Jamil, Fatima Habib, Raheema Kainat (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Ischemic stroke is caused by carotid artery stenosis, often known as carotid artery disease. Stroke is thought to be the leading factor of impairment and the most prevalent and severe neurological condition. For the investigation of intracranial carotid artery disease CT angiography should be preferred. Objective: To assess the carotid artery disease in anterior circulation strokes Methodology: This retrospective study was carried out at the department of medicine, Shalamar Hospital Lahore for a period of two years from January 2019 to April 2021. Simple convenient sampling technique was employed. Totally 356 subjects fulfilling the inclusion criteria were enrolled in the current study. Carotid Doppler USG results were entered in the predesigned Performa. SPSS version 20 was used for analysis of data. Results: In the current study, there were 198 (55.62%) males and 158 (44.38%) females. The average age of the subjects was 62.12 years with standard deviation of 13.1. Amongst the 356 subjects, less than 50% stenosis was observed in 296 (83.14%) patients in the right carotid, 50-69% stenosis in 40 (11.24%) subjects and more than 70% stenosis was observed in 20 (5.62%) subjects in the right carotid while in the left carotid, in 303 (85.11%), 35 (9.83%) and 18 (5.06%) patients, less than 50% stenosis, 50-69% stenosis and more than 70% stenosis was observed respectively. Conclusion: Our study concludes that the frequency of carotid artery disease in anterior circulation strokes is high. For high-risk individuals, Doppler examinations are indicated for both primary and secondary prevention of ischemic stroke. For the investigation of intracranial carotid artery disease CT angiography should be preferred.